MULTI-FUZZY SET RELATIONAL STRUCTURES - Isah, Ahmed Ibrahim (FUDMA JOURNAL OF SCIENCES, 2020)
In this paper, the concepts of multi-fuzzy set relational structures were introduced and some of their properties were presented. Relations were established on both the class of multi-fuzzy sets and on the power multi-fuzzy set of a given multi-fuzzy set. It is demonstrated that as relation on the latter turn out to be a linear order, relations on the former were only partial orders. Some related results were also presented.